The application of new conjugate gradient methods in estimating data - Shoid, Syazni; Shapiee, Norrlaili; Zull, Norhaslinda; Hamizah Abdul Ghani, Nur; Syarafina Mohamed, Nur; Rivaie, Mohd; Mamat, Mustafa (International Journal of Engineering and Technology, 2018)
Many researchers are intended to improve the conjugate gradient (CG) methods as well as their applications in real life. Besides, CG become more interesting and useful in many disciplines and has important role for solving large-scale optimization problems. In this paper, three types of new CG coefficients are presented with application in estimating data. Numerical experiments show that the proposed methods have succeeded in solving problems under strong Wolfe Powell line search conditions.Â